Gaze interaction enhances problem solving: Effects of dwell-time based, gaze-augmented, and mouse interaction on problem-solving strategies and user experience - Roman Bednarik; Tersia Gowases; Markku Tukiainen (Bern Open Publishing, 2009)
It is still unknown whether the very application of gaze for interaction has effects on cognitive strategies users employ and how these effects materialize. We conducted a between-subject experiment in which thirty-six participants interacted with a computerized problem-solving game using one of three interaction modalities: dwell-time, gaze-augmented interaction, and the conventional mouse. We observed how using each of the modalities affected performance, problem solving strategies, and user experience. Users with gaze-augmented interaction outperformed the other groups on several problem-solving measures, committed fewer errors, were more immersed, and had a better user experience. The results give insights to the cognitive processes during interaction using gaze and have implications on the design of eye-tracking interfaces.